Solar panel-powered and convenient-to-assemble and disassemble LED (light-emitting diode) street lamp device and application method thereof - YE MENGJIA (2015)
The invention discloses a solar panel-powered and convenient-assemble and disassemble LED (light-emitting diode) street lamp device and an application method thereof. The device comprises an upright rod (1), a mounting box body (3) for a solar panel and an LED lamp (2), wherein the mounting box body (3) is fixed on the upright rod (1); the LED lamp (2) is detachably connected with the mounting box body (3); a front guide groove (35) and a rear guide groove (36), which extend in the vertical direction, are fixedly formed in the middles of a front side plate (34) and a rear side plate (33) of the mounting box body (3) respectively; the mounting box body (3) is divided into an upper box body and a lower box body (310) by virtue of a horizontal partition plate (32) which is used for fixedly connecting the front side plate (34) and the rear side plate (33) together; the upper box body is used for accommodating the solar panel; and the lower box body (310) is used for accommodating a drive device.